Intraspecific Variation in Plant Growth-promoting Traits of Aureobasidium pullulans - Pei-Feng Sun (Science Faculty of Chiang Mai University, 2019)
Aureobasidium pullulans is a yeast-like fungus exhibiting various morphologies in different niches. It is one of the most widespread saprophyte fungi and is distributed across a wide range of terrestrial and aquatic habitats. Previous studies have reported that A. pullulans can be used as biopesticide. However, the morphological variations may influence its selection as a biocontrol agent. Therefore, knowing the plant growth-promoting (PGP) traits is essential not only for the application as biopesticides but also as biofertilizers. Accordingly, this study was conducted to investigate the different strains of A. pullulans in terms of their PGP traits. All isolates were tested for indole-3-acetic acid, ammonia, and polyamine-producing abilities, calcium-phosphate- and zinc-oxide-solubilizing abilities, and catalase activity. Furthermore, the activities of siderophores and fungal cell wall-degrading enzymes were also assessed. Our results indicated that different strains of A. pullulans exhibited different levels of PGP behavior. This study explored the potential of A. pullulans for promoting plant growth and suppressing fungal plant pathogens.